Selective Inhibition of Ii-dependent Antigen Presentation by Helicobacter pylori Toxin VacA - Molinari, Maurizio (The Rockefeller University Press, 1998)
A major virulence factor in the stomach chronic infection by Helicobacter pylori is a protein toxin (VacA), which alters cell membrane trafficking of late endosomal/prelysosomal compartments. Its role in the chronic infection established by H. pylori is unknown. To test the possibility that VacA alters antigen processing taking place in prelysosomal compartments, we have used the well-established model of antigen processing and presentation consisting of tetanus toxoid–specific human (CD4(+)) T cells stimulated by autologous antigen-pulsed Epstein-Barr virus-transformed B cells. We found that VacA interferes with proteolytic processing of tetanus toxin and toxoid and specifically inhibits the Ii-dependent pathway of antigen presentation mediated by newly synthesized major histocompatibility complex (MHC) class II, while leaving unaffected the presentation pathway dependent on recycling MHC class II. The results presented here suggest that VacA may contribute to the persistence of H. pylori by interfering with protective immunity and that this toxin is a new useful tool in the study of the different pathways of antigen presentation.